Improving Students' Listening Skill Through Watching English Movie For The Eleventh Grade Students Of SMA Dharma Budi Sidamanik - Rohdearni Sipayung; Astri Aristianti (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
Astri Aristianti (17745001). Improving Students' Listening Skill Through Watching English Movie (Classroom Action Research at the Eleven Grade of SMA Dharma Budi Sidamanik, North Sumatra Province, Academic Year 2021/2022). Thesis of the Department of English Education, FKIP, Simalungun University, 2021. The research problem is Does watching English movie can improve listening skill for the eleventh grade students of SMA Dharma Budi Sidamanik ?. The objective of this study was to know whether watching English movie can improve the listening skills of eleventh grade students at SMA Dharma Budi Sidamanik. The sample of this study was the students of class XI MIA 1, consisted 35 students. The research method used is quantitative research; this research is carried out by means of observation, namely the search for data based on facts. Observation and test sheets are data collected during the research. The results obtained show that there is a gradual development and improvement in students' listening skill. The minimum mastery standard for English lessons is 65. The results of the pre-test showed 2 students or 0.05% who achieved the KKM with an average score of 49.1. The results of the post-test showed 35 students or 100% who reached the KKM with an average score of 79.2. In addition, positive responses from English teachers and students were given to the entire research process. Based on the results of these studies, watching English movie can improve students' listening skills